Pengaruh Persepsi Siswa Dan Kepercayaan Diri Terhadap Keterampilan Berbicara Bahasa Inggris (Studi Kasus SMA Swasta Bekasi) - Aprillia aprillia (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Language is a communication tool between members of the community which produced by human utterances. The purpose of language is to convey the intent and willingness to the other person. Education plays an important role in preparing quality human resources. Therefore education should be managed, both in quality and quantity. This can be achieved if students can complete their education on time with good learning outcomes.The data shows that many high school students are poor skilled in English. The main factor for the success of students in the learning process is the teacher. How a teacher delivers teaching material so that students succeed in mastering the material presented is the responsibility of the teacher itself. A teacher's professional competence is a set of abilities that must be possessed by a teacher so that he can carry out his teaching tasks successfully The purpose of this study is to determine the effect of student perceptions on teacher competence and confidence in English language skills  The research method used is the survey method. In this study a sample of 90 students was taken. The technique of data collection is done by distributing questionnaires to objects that will be examined using a Likert scale. The results of the study showed that there was a significant influence between students' perceptions of teacher competence and confidence in English skills.